(untitled) (Western Pacific Surveillance and Response, 2021)
From late December 2019, an outbreak of coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) occurred in Wuhan, China and has spread globally resulting in a pandemic. Brunei Darussalam reported its first case of COVID-19 on 9 March 2020. Several measures were implemented to prevent a national outbreak. We report our experience with surveillance of patients requiring admission in all government hospitals. We detected one positive case, and through contact tracing two further cases were detected. Therefore, without this screening programme, these cases would likely have been missed, leading to further nosocomial and community spread.